Analysis of Epistemological Obstacles Experienced by Indonesian Junior High School Students in Solving Mathematical Literacy Problems viewed from Algebraic Thinking Skills - Nansiana, Millenia Nadhea; Usodo, Budi; Fitriana, Laila (Jurnal Pendidikan Progresif, 2024)
Analysis of Epistemological Obstacles Experienced by Indonesian Junior High School Students in Solving Mathematical Literacy Problems viewed from Algebraic Thinking Skills. The low level of mathematical literacy skills can happen due to learning obstacles. There are various learning obstacles, one of which arises from students' errors or limitations in understanding a particular concept and context of the material, known as epistemological obstacles. One effort to improve mathematical literacy skills is by optimizing algebraic thinking abilities. This is why algebraic thinking is considered a focus of review. However, many students who transition from concrete to abstract thinking experience obstacles in algebraic thinking, including students in grade VIII. This study aims to analyze the epistemological obstacles junior high school students face in solving mathematical literacy problems from the perspective of their algebraic thinking skills. The research method is descriptive qualitative with research subjects of grade VIII junior high schools in Jaten who were then selected two students from each group of high, medium, and low algebraic thinking. The research data includes algebraic thinking ability tests, mathematical literacy tests, and interviews. The study results show that students with medium and low algebraic thinking abilities experienced epistemological obstacles in solving mathematical literacy problems. In contrast, students with high algebraic thinking abilities did not have experienced epistemological obtacles. This study concluded that there are differences in the characteristics of epistemological obstacles between students in the medium and low algebraic thinking ability groups, as identified by the indicators of epistemological obstacles. Keywords: epistemological obstacles, mathematical literacy, algebraic thinkingDOI: http://dx.doi.org/10.23960/jpp.v14.i2.202495